The lichens and allied fungi of forest rocky communities of the Vysokaya (Volda) Mountain (Windy Belt Ridge, Arkhangelsk Region, NW Russia) - Tarasova, Viktoria; Sonina, Angella; Androsova, Vera; Valekzhanin, Andrei; Konoreva, Liudmila (Folia Cryptogamica Estonica, 2020)
The paper presents the results of continuing research of lichen diversity in rocky communities of Windy Belt Ridge (Arkhangelsk Region, NW Russia). Using the method of sample plots and linear routes, the communities of the mountain Vysokaya (Volda) were examined, and 270 species and 2 subspecies of lichens and allied fungi were recorded there. A total of 18 lichens are new for the mainland area of Arkhangelsk Region, 35 species are new to the Vodlozersky National Park (Arkhangelsk part) and 9 species are in the Red Data Book of Arkhangelsk Region (2020). Within sample plots (altogether 0.2 ha), 230 species were found, with 41–50% of total species number being presented within one sample plot (0.04 ha). Along the linear route (2 km), 190 taxa were recorded: 43 species were found only on the route (outside the sample plots), which is 16% of the total lichen species number in studied communities. Comparative analysis of the lichen diversity between currently studied mountains (Olovgora, Muroigora, Vysokaya) of the Windy Belt Ridge showed that the high degree of community conservation, rocky type of communities with significant rocky outcrops, as well as landscape heterogeneity determine conditions for a high species diversity of lichens. In total, 343 species of lichens and allied fungi have been found for the studied mountains of the Windy Belt Ridge.